Disciplines and ideas in the applied social sciences - Cleofe, Myreen P.; Sayuno, Cheeno Marlo M. (Makati City : Diwa Learning Systems, Inc., 2020)
"This textbook is created to help you appreciate the value of involvement in the social sciences, particularly in the fields of counseling, social work, and communication. As a student who are exploring various fields and career opportunities in senior high school, this book offers you a taste and an indulgence of what applied social sciences are all about."
Includes bibliography.
English text.
Keywords: Social sciences; Social sciences -- Study and teaching